2021
DOI: 10.3390/f12081122
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Anatomical Grading and Acoustic–Elastic Properties of Resonant Spruce Wood Used for Musical Instruments

Abstract: This paper deals with the acoustic and elastic properties of resonant wood, classified into four classes, according to the classification of wood quality by the manufacturers of musical instruments. Traditionally, the quality grades of resonant wood are determined on the basis of the visual inspections of the macroscopic characteristics of the wood (annual ring width, regularity, proportion of early and late wood, absence of defects, etc.). Therefore, in this research, we studied whether there are correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Non-destructive ultrasonic testing (US) consists in analysis of material's response at excitation with US waves for evaluation of material properties without inducing damages [13][14][15]. Ultrasound is an elastic wave that propagates in solid, liquid, and gaseous media in excess of 20kHz.…”
Section: Methodsmentioning
confidence: 99%
“…Non-destructive ultrasonic testing (US) consists in analysis of material's response at excitation with US waves for evaluation of material properties without inducing damages [13][14][15]. Ultrasound is an elastic wave that propagates in solid, liquid, and gaseous media in excess of 20kHz.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of the anatomical features of the wood in the construction of the top and back plates of old violins was performed using a WinDENDRO Density image analysis system (Régent Instruments Inc., Québec City, QC, Canada, 2007) from the Department of Forest Engineering, Forest Management Planning and Terrestrial Measurements, Transilvania University of Bras , ov, Romania (Figure 4a,b). The characteristics of the annual rings were measured in terms of the width of the annual rings denoted TRW, the width of the early wood EWW, the width of the late wood LWW and the wavelength of the curly fiber of maple (wavelength CWL) according to the method presented in previous studies [23][24][25]. The annual rings were measured in two or three directions, depending on the objective local difficulties in identifying the contour of the rings, especially for old violins, starting from the edge of the sides to the welding line of the face halves (Figure 4a,b).…”
Section: Wood Structure Data Acquisitionmentioning
confidence: 99%
“…The determination of the anatomical models of the wood structure in the construction of the violins was made by analyzing their top and back plates, determining the characteristics of the annual rings in terms of their width (marked as TRW), the width of the early wood (EWW), the width of the late wood (LWW), and the wavelength of the curled fiber in maple wood (CWL wavelength), according to the methods presented in previous studies [21,22]. For the spruce plates, the width of early wood and late wood was measured along the entire maximum width of the boards, the coating with varnish and the anatomical structure of the wood, making it possible to gather these data.…”
Section: Anatomical Models Of the Wood Structurementioning
confidence: 99%
“…[18][19][20][21]. Many of these musical ins are rare examples of high artistic mastery and are still used as referenc contemporary manufacture of violins [22][23][24]. From this aspect, the determinin have been analyzed over time: the structural quality of wood, moisture conte aging, plate geometry (thickness/arching), finishes used, constructive elemen post, position and shape of acoustic holes, sounding bar, bridge), and string qual studies have highlighted the effect of aging wood and varnish, the contributi primer and even the attack of fungi on the acoustic quality of old violins [25-28 conducted over time on old and new violins show contradictory results: in som the acoustic and dynamic response of old violins is presented as a standard for th of new ones; in other studies in which the acoustic impressions of soloists were through blind tests (without the respondents seeing the violins or knowing thei the results showed that, from the point of view of the acoustic criteria, the ne present a much more appreciated acoustic quality than the old ones [24,29 Regarding old violins, built by well-known luthiers such as Stradivarius, Guarnieri, Amatti, Stainer, Klot and Leeb, there are numerous studies on the structure of wood, its anatomical quality, wood dating, types of varnish used, structural integrity using modern techniques modern, ways of restoration, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation